Co-infusion of high-dose haploidentical donor cells and CD19-targeted CART cells achieves complete remission, successful donor engraftment and significant CART amplification in advanced ALL. (May 2020) - Yu, Changlin; Cai, Bo; Wang, Yao; Wu, Zhiqiang; Hu, Kaixun; Sun, Qiyun; Qiao, Jianhui; Fang, Yanhong; Zuo, Hongli; Wang, Yi; Dong, Zheng; Zhang, Zechuan; et al.
Autologous CD19-targeted chimeric antigen receptor-modified T cells (CD19-CART) remarkably improved the outcome of patients with advanced B-cell acute lymphoblastic leukemia (B-ALL). However, the application and outcomes of allogeneic CART cells is still uncertain. Two patients with advanced B-ALL were enrolled to receive a co-infusion of high-dose human leukocyte antigen-haploidentical donor granulocyte colony-stimulating factor mobilized peripheral blood mononuclear cells (GPBMCs; 21.01–25.34 × 10 8 /kg) and the same donor-derived CD19-targeted CART cells (8.44–22.19 × 10 6 /kg) without additional in vitro gene-editing following a reinduction chemotherapy as precondition. They achieved complete remission and full donor chimerism (FDC) with ongoing 20- and 4-month leukemia-free survival. A significant amplification of donor CART cells was detected in peripheral blood and/or cerebrospinal fluid and was associated with the formation of FDC. The highest amount of copies of the donor CART cells reached 4962 per µg of genomic DNA (gDNA) and 2449 per µg of gDNA, and the longest persistence was 20 months associated with B cell aplasia. Two patients experienced Grade II or III cytokine release syndromes and developed controllable Grade II intestinal acute graft-versus-host disease (GVHD) or limited chronic oral GVHD. High-dose donor GPBMC infusion may enhance amplification and persistence of haploidentical CD19-targeted CART cells, suggesting an alternative therapy for advanced B-ALL patients.